2008
DOI: 10.1097/ccm.0b013e31818094a9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prone position and positive end-expiratory pressure on lung perfusion and ventilation*

Abstract: Positive end-expiratory pressure and posture act synergistically by redistributing lung regional perfusion toward ventral regions, but have antagonistic effects on regional ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…Prone positioning makes the following more homogeneously distributed in the anterior-toposterior direction throughout the lungs: lung densities ( fig. 3) [7,21], as previously discussed; intrapulmonary shunt [22]; lung ventilation [23]; and transpulmonary pressure [24]. By favouring such a homogenisation, prone positioning prepares the lung to receive the strain imposed by mechanical ventilation [25], and hence makes the distribution of the resulting stress more homogeneous across the lung.…”
Section: Ventilator-induced Lung Injurymentioning
confidence: 83%
“…Prone positioning makes the following more homogeneously distributed in the anterior-toposterior direction throughout the lungs: lung densities ( fig. 3) [7,21], as previously discussed; intrapulmonary shunt [22]; lung ventilation [23]; and transpulmonary pressure [24]. By favouring such a homogenisation, prone positioning prepares the lung to receive the strain imposed by mechanical ventilation [25], and hence makes the distribution of the resulting stress more homogeneous across the lung.…”
Section: Ventilator-induced Lung Injurymentioning
confidence: 83%
“…PP improves oxygenation over a variable time course that may reach a plateau after 12-24 h, 26,79,88,89 but in some cases, improvement continues for 30 -55 h 97,98 This has been attributed to the interplay between several factors, including increased IAP and abnormal C CW , compression atelectasis, and persistent small airway closure despite high levels of PEEP (ie, 14 cm H 2 O). 168 Airway closure is both asynchronous in onset and unevenly distributed, particularly in dependent lung regions that delay in opening, close quickly, and have a lower EELV.…”
Section: Incorporating Pp Into Bundled Carementioning
confidence: 99%
“…78 In another experimental ARDS study, application of moderate-level PEEP (10 cm H 2 O) resulted in significant alveolar recruitment in both SP and PP. 79 PEEP caused a redistribution of both ventilation and perfusion toward the dependent lung in both SP and PP. However in SP, PEEPinduced alveolar recruitment occurred only in the dorsal lung, whereas applying PEEP during PP affected alveolar recruitment diffusely down the dorsoventral aspects of the lung.…”
Section: Airway Closure and V A /Q Matching In Experimental Ards And mentioning
confidence: 99%
“…For example, it has been shown that PEEP redistributes the pulmonary blood flow toward dorsal and caudal lung regions in the supine position. 14 In some instances in the present study the values of the P15/P5 ratios were greater than 1. The role of perfusion redistribution may be accounted for in this finding.…”
Section: Relationships Between Change In Density and V Recmentioning
confidence: 84%